Pengaruh Aktivitas Customer Service dan Kepuasan Nasabah terhadap Loyalitas Nasabah Bank Riau Kepri Capem Panam Pekanbaru - Puji Hariyanti; Rahmy Utari (Jurnal Komunikasi, 2013)
Banking industry have hand in glove relevant to its consumer, because relations between client and banking represent one unity. Both of the components is requiring each other. On that account, bank have to earn to give best service to all its clients so that good relation among both parties. In banking industry, the best service is one key for to defend in banking existence. Its applying can be seen in part of office front as strength a bank. For example, officer in part customer service activity will assist client conduct transaction opening of account, denunciating, or request of information concerning banking product.This research used variable customer service activity and satisfication of customer to measure customer loyalty. Object in this research is PT Bank Riau Kepri Capem Panam client. Quantitative analysis in this research is done with reliability test, validity test, and correlation product moment analysis. Result of research indicate that variable customer service activity and satisfaction of customer have connection and influence which are positive to customer loyalty.